EFFECTS OF HEATING TEMPERATURE AND BINDER IN THE PRODUCTION OF CHAR-BASED ELECTRICAL CONDUCTOR - Teguh Endah Saraswati; Achmad Bahrudin; Miftahul Anwar (ALCHEMY Jurnal Penelitian Kimia, 2016)
Graphite as one alotrof carbon is widely used as an electrode material for a good electrical conductivity properties. Charcoal as a carbon source material was found very abundant in nature. Charcoal has the potential application for electrode material in energy storage such as in a battery or supercapacitor. For this purpose, charcoal amorphous structure needs to be converted into a graphite structure so that it has better electrical conductivity property. This research aims to prepare the electrical conductor material derived from wood charcoal that could potentially be used as an electrode. Preparation was made by mixing charcoal powder with asphalt binder with a weight ratio of 3:1, 4:1, 5:1 and followed by heat treatment under an inert atmosphere at temperature of 600°C, 800°C and 1000°C. Charcoal material which was originally to be an electrical insulator has been successfully converted into an electrical conductor. The achievement of the optimum temperature to produce electrodes with the smallest electrical resistance is then applied to the manufacture of carbon electrodes by heating a mixture of charcoal and fructose binder in a weight ratio of 1:1 (w/w). The results showed electrodes with a mixture of charcoal powder and fructose with heat treatment at 1000°C has the better electrical conductivity among other variations.